Analisis Pembangunan Ekonomi terhadap Kemandirian Fiskal di Provinsi Sumatera Barat - Jean Elikal Marna; Gusma Yeni; Hefrizal Handra; Efa Yonnedi (Universitas Negeri Padang, 2022)
This study aims to find out how fiscal independence and economic development in the province of West Sumatra can affect regional development in the province of West Sumatra, by testing the effect of economic growth, poverty rates and unemployment rates on fiscal independence in the province of West Sumatra in 2011-2020. This type of research is a quantitative descriptive research. This study uses an analytical model of multiple regression analysis techniques. The data used in this study is secondary data with the nature of time series data from 2011-2020 obtained from the Central Bureau of Statistics (BPS). The results of this study indicate that: the economic growth variable has a significant effect on fiscal independence, and the unemployment rate variable also has an effect on fiscal independence in the province of West Sumatra, while the poverty rate variable has a negative and insignificant effect on the fiscal independence of the province of West Sumatra